Innovating Kitchen Waste into Liquid Gold: Rice-Washing Water MOL Innovation for Eco-Friendly Liquid Organic Fertilizer in Kuala Lumpur, Malaysia - Neni Marlina; Rahmat Kurniawan; Puri Pratama Ardina Ningrum; Inneke Abdillah Fahmi; Sisvaberti Apriyatna; Khalisah Hayatudin; Helmizuryani Helmizuryani; Gusmiatun Gusmiatun; Nurbaiti Amir; Erni Hawayanti; Maria Lusia; Ahmad Sofian; Dessy Tri Astuti (Altifani Journal: International Journal of Community Engagement, 2026)
The problem of kitchen waste, such as vegetable and fruit scraps, in urban areas is increasing with population growth and urbanization in various cities in Malaysia. Furthermore, organic waste such as rice washing water (leri water) is generally discarded, despite its great potential as a raw material for Local Microorganisms (LMICs) in the production of liquid organic fertilizer from kitchen waste. This community service article aims to describe the innovation of processing leri water into environmentally friendly liquid organic fertilizer from kitchen waste through training. This program was implemented at the Muhammadiyah Kepong Guidance Center, Kuala Lumpur, Malaysia, in January 2026. The methods used were outreach and the production of Leri water MOL. The results of the activity showed an increase in the knowledge and skills of children at the Muhammadiyah Kepong Guidance Center in processing kitchen waste into useful organic fertilizer, supporting household food security, and reducing urban organic waste.